Perbandingan Pengujian Usability pada Penggunaan Thumbnail di Personal Website - Susilo, Edi; Tristianingsih, Purwandari Nur (JURNAL FASILKOM, 2024)
The personal website is a type of website that can be managed by individuals. In order for a personal website to have an attractive design, it is necessary to consider several factors in its user interface design, one of which is related to thumbnails. Whether thumbnails on content need to be added or not. However, research related to the application of thumbnails, especially on personal websites, has not been found. This study will test personal website designs that use thumbnails on content and personal website designs without using thumbnails. Both are tested using the same tool, namely usability testing. Usability testing uses the SUS questionnaire tool. The SUS questionnaire has 10 questions and will be distributed to 20 respondents for each design. 20 respondents who will test personal website designs that use thumbnails on content and 20 more respondents will test personal website designs without using thumbnails on content. Based on the distribution of questionnaires, the results of testing personal website design by applying thumbnails obtained an average SUS score of 72. While the results of testing personal website design without applying thumbnails obtained an average SUS score of 76. Based on the results of usability testing, the scores obtained are not too different. Both are in the same grade which is C and acceptable. In general, when designing a personal website, you can choose to use thumbnails on the content or not use them. Future research can compare the assessment by testing user experience and both designs. This is to see in terms of attractiveness and aesthetics of personal website design whether there is a difference if applying thumbnails or without thumbnails.